Overcoming immunosuppression in bone metastases. (September 2017) - Reinstein, Zachary Z.; Pamarthy, Sahithi; Sagar, Vinay; Costa, Ricardo; Abdulkadir, Sarki A.; Giles, Francis J.; Carneiro, Benedito A.
Abstract: Bone metastases are present in up to 70% of advanced prostate and breast cancers and occur at significant rates in a variety of other cancers. Bone metastases can be associated with significant morbidity. The establishment of bone metastasis activates several immunosuppressive mechanisms. Hence, understanding the tumor-bone microenvironment is crucial to inform the development of novel therapies. This review describes the current standard of care for patients with bone metastatic disease and novel treatment options targeting the microenvironment. Treatments reviewed include immunotherapies, cryoablation, and targeted therapies. Combinatorial treatment strategies including targeted therapies and immunotherapies show promise in pre-clinical and clinical studies to overcome the suppressive environment and improve treatment of bone metastases.